Developing Agreed and Accepted Understandings of Spirituality and Spiritual Care Concepts among Members of an Innovative Spirituality Interest Group in the Republic of Ireland. - Brady, Vivienne (My University, 2016)
A Spirituality Interest Group (SIG) was set up in in the School of Nursing and Midwifery, Trinity College Dublin, Republic of Ireland (ROI), in March 2013. This paper reports on some of the journey and requirements involved in developing the group. It highlights the essential work of establishing agreed understandings in an objective way in order for the group to move forward with action. These agreed understandings have contributed to the group’s success. Outlining the group’s journey in arriving at agreements may be of use to others considering creating similar groups. One key action taken to determine the suitability of the group’s aims and terms of reference was the distribution of a Survey Monkey to group members (n = 28) in 2014. One early meeting of the group discussed future goals and direction using the responses of this anonymous survey. This paper reports on the results of the survey regarding the establishment of the SIG and the development of a shared understanding of spiritual care among the members. There is consensus in the group that the spiritual care required by clients receiving healthcare ought to be an integrated effort across the healthcare team. However, there is an acceptance that spirituality and spiritual care are not always clearly understood concepts in practice. By developing shared or at least accepted understandings of spirituality and spiritual care, SIG hopes to be able to underpin both research and practice with solid foundational conceptual understanding, and in the process also to meet essential prerequisites for achieving the group’s aims.
PUBLISHED
Keywords: spirituality; spiritual; spiritual care; interdisciplinarity; health